1987
DOI: 10.1172/jci112772
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin enhances tissue factor and suppresses thrombomodulin expression of human vascular endothelium in vitro.

Abstract: Endotoxemia is frequently associated clinically with disseminated intravascular coagulation (DIC); however, the mechanism of endotoxin action in vivo is unclear. Modulation of tissue factor (TF) and thrombomodulin (TM) expression on the endothelial surface may be relevant pathophysiologic mechanisms. Stimulation of human umbilical vein endothelial cells with endotoxin (1 ,ug/ml) increased surface TF activity from 1.52±0.84 to 11.89±8.12 mU/ml-106 cells at 6 h (n = 11) which returned to baseline by 24 h. Repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
213
0
4

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(227 citation statements)
references
References 46 publications
(33 reference statements)
8
213
0
4
Order By: Relevance
“…Expression of Tm decreases on vascular endothelium in vitro and in vivo 66,67 after treatment with endotoxin via TNF-␣ up-regulation and signaling. Increased soluble Tm (sTm) values were observed in septic DIC models, 68 which supports our observations.…”
Section: Discussionmentioning
confidence: 98%
“…Expression of Tm decreases on vascular endothelium in vitro and in vivo 66,67 after treatment with endotoxin via TNF-␣ up-regulation and signaling. Increased soluble Tm (sTm) values were observed in septic DIC models, 68 which supports our observations.…”
Section: Discussionmentioning
confidence: 98%
“…CAT and ␤-Galactosidase Assays and Measurement of TM Antigen Level-For measurement of CAT activity, 1-deoxy[dichloroacetyl- [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]chloramphenicol was used as the substrate, and the 3Ј-acetylated form of chloramphenicol was detected by autoradiography following thin layer chromatography on a Silica Gel 60 plate using a solvent of chloroform/methanol (19:1, v/v). ␤-Galactosidase activity was measured according to Promega's protocol, and the activity was used as an internal control to normalize the transfection efficiency of individual pTM-CAT plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…TM expression of human endothelial cells is decreased by tumor necrosis factor-␣ (4 -6), interleukin-1 (6, 7), endotoxin (8), and phorbol ester (5,6) and oxidized LDL (9, 10), but we have found that it is increased by all-trans-retinoic acid (t-RA) (11,12) and/or cAMP (11,13) in human umbilical vein endothelial (HUVE) cells, through the acceleration of transcriptional activity. Several studies on the regulatory region of human TM gene have been reported (14 -17), and Dittman et al (17) showed the existence of an RA response element (RARE) in the 5Ј-flanking region of the gene.…”
Section: Thrombomodulin (Tm)mentioning
confidence: 99%
“…26 During sepsis, the endothelium shifts from an anticoagulant surface to a procoagulant surface by reduced expression of anticoagulatory molecules such as thrombomodulin, thereby shifting the action of thrombin towards the cleavage of fibrinogen and the generation of fibrin clots. 27,28 Furthermore, LPS may directly induce the prothrombotic state by upregulating the endothelial expression of tissue factor through an NF-kB-dependent mechanism. 29 These changes contribute to the disseminated intravascular coagulation characteristic of sepsis.…”
Section: Hemostasismentioning
confidence: 99%